2001
DOI: 10.1002/ijc.1035
|View full text |Cite
|
Sign up to set email alerts
|

Changing face and different countenances of prostate cancer: Racial and geographic differences in prostate‐specific antigen (PSA), stage, and grade trends in the PSA era

Abstract: SUMMARY The purpose of this investigation was to examine changes in pretreatment prostate-specific antigen (PSA), stage, and grade over the past decade as a function of race and geographic region. A multiinstitutional database representing 6,790 patients (1,417 African-American, 5,373 white) diagnosed with nonmetastatic prostate cancer between 1988 and 1997 was constructed. PSA, stage, and grade data were tabulated by calendar year and region, and time trend analyses based on race and region were performed. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…These stage and PSA trends are largely consistent with those reported previously. [2][3][4] The relatively consistent proportion of cases diagnosed with PSA less than 4 ng/ml, including many that have intermediate or high risk features based on Gleason score and/or T stage, underscores the continued importance of digital rectal examination in detecting cases that are falsenegative by PSA screening alone. 13 Overall, we found a trend toward higher Gleason scoring with time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These stage and PSA trends are largely consistent with those reported previously. [2][3][4] The relatively consistent proportion of cases diagnosed with PSA less than 4 ng/ml, including many that have intermediate or high risk features based on Gleason score and/or T stage, underscores the continued importance of digital rectal examination in detecting cases that are falsenegative by PSA screening alone. 13 Overall, we found a trend toward higher Gleason scoring with time.…”
Section: Resultsmentioning
confidence: 99%
“…1 PSA screening has effected downward biochemical and clinical stage migrations, with the result that a given newly diagnosed prostate cancer is likely to be of lower stage and associated with a lower serum PSA than previously. [2][3][4] On the other hand, recent reports have illustrated a trend during the last decade toward upgrading in terms of Gleason scoring. 5 The risk assessment system devised by D'Amico et al assigns patients to low, intermediate or high risk groups based on clinical T stage, serum PSA and Gleason score.…”
mentioning
confidence: 99%
“…6 The widespread prevalence of PSA screening for prostate cancer has led to a significant migration toward lower stage, lower risk tumors. 7,8 As the majority of tumors encountered in today's practice are cT1c lesions, there is less stratification by clinical stage than had been seen in the past. Additionally, it has been shown that numerous clinical variables including pretreatment PSA, biopsy Gleason score and PPB are strong predictors of biochemical recurrence after radical prostatectomy, potentially stronger than clinical T stage.…”
mentioning
confidence: 99%
“…1 Early detection of cases has produced downward stage migration at presentation. 2,3 Earlier diagnosis and therapeutic advances have facilitated the increased use of aggressive local treatment, particularly radical prostatectomy (RP), external beam radiotherapy (EBRT) and more recently interstitial radiotherapy (brachytherapy). 3 Evidence increasingly demonstrates a decrease in prostate cancer mortality with local treatment of low stage disease.…”
mentioning
confidence: 99%